PENERAPAN MULTIMEDIA AUDIO GALERY ILEARNING COMMUNITY AND SERVICES (MAGICS) SEBAGAI MEDIA PENYIMPANAN DOKUMENTASI PADA PERGURUAN TINGGI RAHARJA - Hani Dewi Arriesanti; Muhamad Yusup; Ceria Marcelina (CCIT Journal, 2014)
Technology information had a critical role in human life, no exception in education. One of the products technology that is occupied in education is multimedia. Perguruan Tinggi Raharja which applies the methods of iLearning need multimedia in realizing concept 4B. The application of multimedia was meant to make efficiency and effectiveness in the procurement information in form of documentation such as image, audio, and video. However Green Documentation as a file storage in Perguruan Tinggi Raharja is still less than optimal, so the documentation is spread across multiple storage online media. This is because either Green Documentation and media online were available haven't been enough to be storage requirements which covers images, audio, and video in one integrated place that you can share. As a result, students having trouble finding documentation of activities held by the campus. MAGICS is an online media which allows all documentation can be arranged neatly to facilitate searches. This paper tries to describe the problems and solving in an information systems, especially in terms of documentation. Implementation of MAGICS can be used as a solution for providing file storage and file sharing in the application of learning method (iLearning).